Phytoestrogen α-Zearalanol Improves Memory Impairment and Hippocampal Neurogenesis in Ovariectomized Mice - Dong, Yilong (Hindawi Publishing Corporation, 2014)
Estrogen is known to provide robust protection of memory in postmenopausal women, but the fact that estrogen may increase the incidence of uterine and breast tumors has undoubtedly limited the clinical use of estrogen. In the present study, the effect of α-zearalanol (α-ZAL), a plant-derived phytoestrogen with low side-effect on uterine and breast, on memory has been evaluated in ovariectomized (OVX) mice when using 17β-estradiol (17β-E2) as an estrogen positive control. Our findings demonstrated that OVX resulted in impaired spatial learning and memory and reduced numbers of newborn neurons in the dentate gyrus of the hippocampus, while 17β-E2 or α-ZAL treatment significantly improved memory performance and restored hippocampal neurogenesis. We also found the reduction of brain derived neurotrophic factor (BDNF) and TrkB expression in OVX mice, which were ameliorated by 17β-E2 or α-ZAL supplementation. These results indicated that α-ZAL may improve memory impairments induced by OVX and modulate the expression of BDNF-TrkB benefit to neurogenesis which may be involved in the memory protection from α-ZAL, in a manner similar to that of 17β-E2. The present findings suggested that α-ZAL may be a plausible substitute of 17β-E2 in improving memory in postmenopausal women.